Determining breast cancer recurrence following completion of active treatment: A novel approach using linked administrative health data. (2017) - Preen, David; Kemp-Casey, Anna; Roughead, Elizabeth; Lopez, Derrick; Bulsara, Max; Boyle, Frances; Saunders, Christobel
No abstract available